Treatment outcomes of laser therapy in oral submucous fibrosis-a systematic review - Dr Shailesh M. Gondivkar; Dr Amol R. Gadbail; Dr Sachin C. Sarode; Dr Rima S. Gondivkar; Shankargouda Patil; Dr Rahul N. Gaikwad; Dinh-Toi Chu; Dr Monal Yuwanati (Elsevier, 2020)
Background: The mainstay of oral submucous fibrosis (OSF) management is to increase the mouth opening; thereby improving oral functionalities. In modernized dentistry, laser therapy (LT) could play a major role for trismus relief in OSF patients. The present review was performed to systematically analyze the published literature on LT for OSF management. Methods: PubMed, Scopus, Web of Science and CINAHL databases were searched until June 2019 using suitable key words and the information was extracted according to the PRISMA guidelines. All full text papers that assessed efficacy of LT for OSF management without limitations on age, gender, ethnicity, or socioeconomic status of the participants were considered eligible. Participants were allocated to the LT alone or in adjunct to oral physiotherapy and medicinal treatment. Outcome parameters included the reduction in trismus. Review articles, case reports, editorial, conference abstracts and in vitro studies were excluded. No restriction was applied on date and language of the publications. Results: Out of 97 published papers, 7 studies met the inclusion criteria and were included for the analysis. All the studies were clinical and mainly included stage II and III OSF patients. Although different laser types and other parameters were used, all the studies reported improvement in mouth opening in the range of 6.84 mm and 23.7 mm. Additionally, two studies noticed reduced burning sensation and increased tongue protrusion and cheek flexibility. Conclusion: The LT can provide a promising and better means for relieving trismus and probably OSF-related other symptoms in moderate stages of the disease.